Does the Use of Solid Cooking Fuels Increase Household Out-Of-Pocket Medical Expenses? Evidence from Indonesia - Siagian , Theo Ojahan Pardamean; Hartono, Djoni (Journal of Indonesian Economy and Business, 2025)
Introduction/Main Objectives: The objective of this study is to assess how the utilization of solid cooking fuels influences out-of-pocket medical expenses incurred by households in Indonesia. Background Problems: Solid cooking fuel use remains prevalent in Indonesia, negatively impacting the health of household members, and consequently affecting associated medical expenses as well. Novelty: To the best of the authors’ understanding, this study is the first to explore how the use of solid cooking fuels affects the out-of-pocket medical expenses of households in Indonesia. Research Methods: This study employs instrumental variables to address existing endogeneity issues. Finding/ Results: On average, households using solid cooking fuels show a 0.0041 increased proportion of out-of-pocket medical expenses to total household expenditure compared to households using non-solid cooking fuels. Conclusion: The Indonesian government can reduce household medical expenses by improving the use of cleaner cooking fuels. Implementable policies include providing assistance with clean energy cooking equipment and ensuring the availability of clean energy in areas in need.